Profile of Sports Injuries: A Descriptive Analysis of Student-Athletes in Bengkulu City - Bayu Insanistyo; Tono Sugihartono; Arief Ibnu Haryanto; Nurul Fajar Muslimah Ningrum; Yahya Eko Nopiyanto; Yarmani Yarmani; Jerome Angelitud Porto (Universitas Sriwijaya, 2026)
Injuries represent a major risk factor affecting the performance and long-term development of student-athletes. However, empirical data on injury patterns and injury management knowledge among student-athletes in local contexts remain limited. This study aimed to analyze the injury profile in terms of type, location, and cause of injury, as well as the knowledge of injury management in student athletes in Bengkulu City. Methods: A quantitative descriptive method using a survey technique. Fifty-three student athletes from 9 sports were sampled using purposive sampling. The instruments consisted of a multi-response questionnaire and a multiple-choice test that had undergone validity, reliability, difficulty, and item difference tests. Data were analyzed descriptively using percentages. Results: A total of 137 injuries were recorded among student athletes in Bengkulu City, with sprains (29%), bruises (23%), and strains (21%). The lower extremities, with the ankle area (15.33%), were the most common injury sites. Most injuries occurred during training (83%), with the primary cause being external violence (39.63%), such as high-impact or high-intensity sports, and the condition of the infrastructure. Knowledge of injury management was categorized as